2009
DOI: 10.1017/s0016756809005974
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the offshore flood basalt sequence using onshore volcanic facies analogues: an example from the Faroe–Shetland basin

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 41 publications
2
77
0
Order By: Relevance
“…Saunders et al 1997;Hansen et al 2009;Jerram et al 2009;Brooks 2011;Nelson et al 2015). Along East Greenland this opening propagated northwards to the Norwegian-Greenland Sea and led to plate separation occurring during the Eocene (c. 55 Ma), and was accompanied by widespread igneous activity along 2000 km of the conjugate rifted margins (e.g.…”
Section: Volcanic History Of East Greenland and The Jameson Land Basinmentioning
confidence: 99%
“…Saunders et al 1997;Hansen et al 2009;Jerram et al 2009;Brooks 2011;Nelson et al 2015). Along East Greenland this opening propagated northwards to the Norwegian-Greenland Sea and led to plate separation occurring during the Eocene (c. 55 Ma), and was accompanied by widespread igneous activity along 2000 km of the conjugate rifted margins (e.g.…”
Section: Volcanic History Of East Greenland and The Jameson Land Basinmentioning
confidence: 99%
“…Berndt et al, 2001). These peculiar volcanic successions display a large variety of seismic facies that are indicative of the style of volcanic emplacement, depositional environment and subsequent mass transport Planke et al, 2000;Brendt et al, 2001;Jerram et al, 2009;Wright et al, 2012;Abdelmalak et al, Submitted). The volcanic sequences emplaced during the onset of the breakup, partially masked seismically the Late Cretaceous-Eocene and older sedimentary strata and continental structures inferred in the outermost part of the Vøring Margin.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…It is noteworthy that Jerram et al (2009) have shown significant thicknesses of hyaloclastite in FaroeShetland basin of the NAIP, which also occur onshore in Greenland, pointing to significant parts of the area not having significant uplift, and therefore complicating the simple plume model in the NAIP example. The domal uplift model may become significantly modified resulting in regions of crustal dilation and contraction.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%